Pengembangan Sistem Pelatihan Jarak Jauh Berbasis Moodle di Balai Diklat Keagamaan Bandung - Dedi Restendi; Firman Nugraha; Agus Trianto (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[MOODLE BASED DISTANCE TRAINING SYSTEM DEVELOPMENT IN BALAI DIKLAT KEAGAMAAN BANDUNG]. Developing online training system is essential to create equalization over training opportunities, enrich learning materials, and increase trainees participation in learning. The development is also a medium to create accessible learning environment. Online training requires learning management system. One of the most widely used applications is Moodle. It has the latest version that can be used to improve online training’s quality, namely Moodle version 3.7.1. This study aims to find out Moodle-based remote training system implementation at Bandung Religious Training Center in 2020. Research and Development waterfall model is applied. Application testing is by using blackbox techniques. The analysis uses SCORM and Haughey theory. The result showed that Moodle-based remote training is considered good based on black box tests. It can be seen from several aspects of websites, such as appearance and content, implementation, institutional readiness, as well as facilities and infrastructure. Moodle 3.7.1 based remote training websites are recommended for socialization and provided remote training manual instructions